Low voltage electron microscopy : principles and applications - Bell, D. C. (David C.); Erdman, Natasha (Chichester, West Sussex, United Kingdom : Wiley, Published in association with the Royal Microscopical Society, 2013)
"The book describes the recent advances in the area of low-voltage electron microscopy, covering topics in TEM, SEM, STEM"--